Effect of preparation method on Co-B catalytic activity for hydrogen generation from alkali NaBH4 solution - Jeong, S. U.; Cho, E. A.; Nam, S. W.; Oh, I. H.; Jung, U. H.; Kim, S. H. (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
A Co-B catalyst is used to generate hydrogen from alkaline aqueous NaBH4 solutions. This study examined the properties of a CO-B catalyst prepared using different precursors (COCl2 and CoSO4) and NaBH4/CO2+ mole ratios (0.67, 1.5, 3) at calcination temperatures of 130, 250 and 450 degrees C. As the calcination temperature was increased in N-2 atmosphere mixed with 1% air, the typical amorphous structure of Co-B disappeared and the X-ray diffraction peaks corresponding to Co3O4 became sharper. Metallic Co was formed when a NaBH4/CO2+ mole ratio of 3 was used as the reductant with a corresponding reduction in the rate of H-2 generation. The highest level of H-2 generation (2400 ml/min g) was obtained with CoCl2 as the precursor, a NaBH4/CO2+ mole ratio of 1.5 as the reductant, and a calcination temperature of 250 degrees C. (C) 2006 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: SODIUM-BOROHYDRIDE; HYDROLYSIS; COBALT; METAL; BORIDE; IONS